Framing Analysis of News Coverage on the Budget Blocking of the Nusantara Capital City Development in Detik.com and Tempo.co - Ririn Puspita Tutiasri; Mohammad Syarrafah; Muhammad Febriyanto (International Journal of Social, Economic, and Business, 2025)
The 2024 Indonesian presidential election, won by the Prabowo Subianto–Gibran Rakabuming Raka ticket, marked the beginning of the implementation of massive budget efficiency policies. One of the impacts was the blocking of the budget for a strategic national project, namely the construction of the new capital city, Nusantara (IKN), which sparked public debate and became the focus of online media. Given that media plays a vital role in shaping public perception and opinion, this study aims to analyze how media framing is conducted by Detik.com and Tempo.co in framing the issue of the IKN budget freeze. This study uses the framing model proposed by Zhongdang Pan and Gerald M. Kosicki, which includes four main elements: syntax, script, thematic, and rhetorical. The method used is qualitative descriptive with a constructivist paradigm, which views social reality as the result of intersubjective construction. Data was collected through an analysis of news articles published by Detik.com and Tempo.co between February 6 and 27, 2025, focusing on the issue of the IKN budget freeze. The results of the study indicate that Tempo.co employs a critical framing strategy, emphasizing fiscal uncertainty, environmental impacts, and inconsistencies in government policy. Meanwhile, Detik.com tends to present an informative and administrative frame, emphasizing the continuity of development and clarifications from state authorities. These framing differences indicate distinct editorial orientations between the two media outlets. These findings confirm that framing and agenda setting are not only influenced by objective facts but also by ideological preferences and structural interests inherent in the media institutions themselves.